2010
DOI: 10.1080/09583151003599708
|View full text |Cite
|
Sign up to set email alerts
|

Key elements in the successful control of diapausing codling moth,Cydiapomonella(Lepidoptera: Tortricidae) in wooden fruit bins with a South African isolate ofHeterorhabditis zealandica(Rhabditida: Heterorhabditidae)

Abstract: The non-insecticidal control strategies currently being implemented in South African orchards for the control of codling moth, Cydia pomonella (L.) may be hampered by wooden fruit bins being infested with diapausing codling moth larvae, acting as a potential source of re-infestation. Key factors contributing to the success or failure of an entomopathogenic nematode application were investigated using the SF 41 isolate of Heterorhabditis zealandica in laboratory bioassays with wooden minibins. Under operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Of all, S. yirgalemense performed the best with the highest mortality, followed by H. zealandica, which was the same South African isolate as that has been used against codling moth (De Waal et al, 2010. In this study pupae of FCM were found not to be not as susceptible as larvae and needed fourfold the concentration of 200 IJ/pupae to give mortality of between 20 and 75% in comparison for larvae where a concentration of 50 IJ/larvae gave mortality of 77-100%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of all, S. yirgalemense performed the best with the highest mortality, followed by H. zealandica, which was the same South African isolate as that has been used against codling moth (De Waal et al, 2010. In this study pupae of FCM were found not to be not as susceptible as larvae and needed fourfold the concentration of 200 IJ/pupae to give mortality of between 20 and 75% in comparison for larvae where a concentration of 50 IJ/larvae gave mortality of 77-100%.…”
Section: Discussionmentioning
confidence: 97%
“…Both S. yirgalemense and H. zealandica showed promise as biological control agents in laboratory bioassays against FCM larvae, pupae and emerging moths. In addition, H. zealandica has also been found to be highly virulent against codling moth (Cydia pomonella, L.) diapausing larvae residing beneath the bark of apple trees as an aerial application (De Waal et al, 2010. The biology of FCM offers a window of opportunity for application of EPN to the soil.…”
Section: Discussionmentioning
confidence: 98%
“…Entomopathogenic nematodes (EPNs) of the genera Heterorhabditis Poinar (Rhabditidomorpha: Strongyloidea) and Steinernema Travassos (Panagrolaimomorpha: Strongyloidoidea) are safe biological control agents (Ehlers 2003) widely used in integrated pest management of insect pests in soil or cryptic habitats (e.g., Dembilio et al 2009;de Waal et al 2010;Martinez de Altube et al 2008;Toepfer et al 2010). EPN can be mass produced in industrial scale bioreactors (Ehlers 2001;Hirao and Ehlers 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these pests include citrus root weevils in citrus, black vine weevils in nurseries, mole crickets on turf grass, peach borer and codling moth on apples and black cutworms on turf and vegetables (Klein 1990;Georgis & Hague 1991;Kaya & Gaugler 1993). In South Africa, research on the use of EPNs has mainly been done on the control of codling moth (De Waal et al 2010, 2011a; mealybug (Stokwe 2009;Le Vieux & Malan 2013;Van Niekerk & Malan 2013); the banded fruit weevil (Ferreira & Malan 2013); and false codling moth . These insects are predominantly pests on deciduous fruit, citrus and in vineyards.…”
Section: The Role Of Entomopathogenic Nematodes As Biological Controlmentioning
confidence: 98%